INVERSE KLIPPEL-TRENAUNAY SYNDROME - Santino,Mariana Franco Ferraz (2020)
ABSTRACT Objective: To report a rare case of inverse Kipplel-Trenaunay. Case description: A 16-year-old girl with a grayish-depressed plaque on her left thigh. Angioresonance showed a vascular malformation affecting the skin and subcutaneous tissue. Comments: Inverse Klippel-Trenaunay is a Klippel-Trenaunay syndrome variation in which there are capillary and venous malformations associated to hypotrophy or shortening of the affected limb. Modifications on the limb’s length or width result from alterations in bones, muscles, or subcutaneous tissues. It has few described cases. Further clinical and molecular studies must be performed for a proper understanding.